(untitled) (Research, Society and Development, 2022)
Fibrinolytic enzymes are proteases that are capable of degrading the fibrin mesh present in blood clots and can be obtained through fungal extracts. Thus, the objective of this paper was to seek out and compare all the information regarding the production and biochemical characterization of fibrinolytic enzymes of mushroom species published in papers in the last ten years. The research was carried out in eight national and international electronic databases using the terms: “fungal enzymes”, “fibrinolytic Proteases”, “thrombosis” and “mushrooms”. The results obtained were analyzed according to each step. In the first stage, the titles and abstracts of all papers were analyzed independently; in the second stage, all papers were read and those that did not meet the inclusion criteria were excluded. Then, the remaining papers were reviewed and the data were tabulated and compared. As a result, it was found that enzymes with fibrinolytic action were obtained from eight species of mushrooms in the period of this research: P. sajor-cashew, P. ferulae, P. ostreatus, L. shimeji, A. polytricha, H. erinaceum, C. comatus and C. militaris. The enzymes were identified as protease SPPs, metalloproteases, serine proteases and serine metalloproteases. The methods used to evaluate fibrinolytic activity were the fibrin plate method and/or the formation of artificial thrombus through thrombin and fibrinogen. The molecular mass of these enzymes ranged from 18 to 66 kDa and, for the biochemical characterization of the extracts, the pH ranged from 4.0 to 9.5 and the optimum temperature from 25 to 70 ºC. Via the review, it was observed that few articles were published on the subject in question, which made it necessary to carry out more studies to discover the biotechnological properties of mushrooms and define their applications in the most diverse sectors of industries, not only in commercial species of mushrooms, but also in native species.